Din eğitimi bilimi bağlamında hermenötik ve din dili tartışmaları - Parlak, Sıdıka Nur (My University, 2025)
Din eğitimi bilimi pek çok disiplinin kesişim alanında yer alır ve bu kesişim alanında ortaya çıkan yeni sorulara cevap arar. Din dili konusu da bunlardan biridir. Bu tez, din eğitimi bilimi çerçevesinde, din dili kavramını felsefi hermenötik bir zeminde çözümleyerek din eğitiminin felsefi temellerine katkı sunmayı amaçlamaktadır. Öncelikle dil, düşünce, kültür ve din arasında bağlantı kurulmuş, din dili kavramı açıklanmıştır. Ülkemizde ve Batı’da din eğitimi bağlamında yapılan çalışmalar incelenmiş, din dili ifadesinin hangi anlamda kullanıldığı tespit edilmeye çalışılmıştır. Din eğitimi biliminin din dili konusunda hangi alanlarda çalışma yaptığı/ yapabileceği tasnif edilmiştir. Bu tasnif sonucunda konunun din eğitimcisi gözüyle tartışılacak bir açıklığa kavuşturulması beklenmektedir. Nitel araştırma yöntemiyle planlanan bu tezde, literatür incelemesine dayanan betimsel bir model tercih edilmiştir. Din dili ifadesinin ülkemizde -din eğitimi çatısı altında- çoğunlukla dilin işlevsel yönüyle kullanıldığı ve dini iletişim becerilerini karşıladığı görülmüştür. Batı’da ise din dili, felsefi hermenötik düşünme döngüsünün bir ögesi olarak kabul edilmiştir. Klasik, analitik ve eleştirel eğitim felsefelerinin en önemli teorilerinden biri olan yapılandırmacılığın arka planında yer alan hermenötiğin, modern/ postmodern din eğitimi yaklaşımlarına tesir ettiği düşünülmektedir. Yapılandırmacılığın din eğitimi uzantısı olan dinden öğrenme modelinde de eleştirel düşünme, anlama, yorumlama, eyleme dönüştürme, din okuryazarlığı gibi beceriler öncelenmektedir. Bu diyalojik becerilere dönük uygulama alanı oluşturabilmek için dilin tüm yönleriyle ve yorum geleneğiyle bağlantılı incelenmesi gerekmektedir. Bu bağlamda -kendi geleneğimiz çerçevesinde- anlamayı ve yorumlamayı esas alan çalışmalar yapılmadan günümüz çalışmalarının “etkili din dili” önerisine dair yeterli bir çıkarım sağlamak zor görünmektedir.

Religious education as a discipline exists at the intersection of multiple academic fields and seeks to address the emerging questions arising from this intersection. One such issue is the concept of religious language. This thesis aims to contribute to the philosophical foundations of religious education by analyzing the concept of religious language within the framework of philosophical hermeneutics. Initially, connections between language, thought, culture, and religion were established and the concept of religious language was explained. Studies conducted in both Turkey and the West within the context of religious education are examined to determine the contexts in which the term religious language is used. An attempt was also made to classify the areas in which religious education as a discipline has been or could potentially be involved in research on religious language. Through this classification, this issue is expected to be clarified from the perspective of religious educators. In this thesis, which was planned using a qualitative research method, a descriptive model based on literature review was preferred. The findings indicate that in Turkey, the term religious language is used in the context of religious education mainly in relation to its functional aspects, especially in addressing religious communication skills, whereas in Western contexts, religious language is considered as an element of the philosophical-hermeneutic cycle of thought. Hermeneutics, which underpins constructivism -one of the most significant theories in classical, analytical, and critical philosophies of education- has influenced both modern and postmodern approaches to religious education. The learning from religion model, which represents the constructivist extension of religious education, skills such as critical thinking, comprehension, interpretation, transformation into attitude and religious literacy are emphasized. To establish a field of application for these dialogical skills, religious language needs to be studied in all its dimensions and in relation to the tradition of interpretation. In this context, without studies based on understanding and interpretation -within the framework of our own interpretation- it seems difficult to provide an adequate conclusion about the “effective religious language” proposal of today's studies.
Hermeneutics and religious language debates in the context of religious education science
Keywords: Din; Din Dili; Din Eğitimi Bilimi; Felsefi Hermenötik; Hermeneutics; Hermenötik; Öğrenim ve öğretim; Philosophical Hermeneutics; Religion; Religious Education Science; Religious Language; Study and teaching; Tefsir bilimi; Turkey; Türkiye